Pilot study of atomoxetine in patients with Parkinson's disease and dopa-unresponsive Freezing of Gait. Issue 1 (December 2015) - Revuelta, Gonzalo; Embry, Aaron; Elm, Jordan; Gregory, Chris; Delambo, Amy; Kautz, Steve; Hinson, Vanessa
Abstract Background Freezing of gait (FoG) is a common and debilitating condition in Parkinson's disease (PD) associated with executive dysfunction. A subtype of FoG does not respond to dopaminergic therapy and may be related to noradrenergic deficiency. This pilot study explores the effects of atomoxetine on gait in PD patients with dopa-unresponsive FoG using a novel paradigm for objective gait assessment. Findings Ten patients with PD and dopa-unresponsive FoG were enrolled in this eight-week open label pilot study. Assessments included an exploratory gait analysis protocol that quantified spatiotemporal parameters during straight-away walking and turning, while performing a dual task. Clinical, and subjective assessments of gait, quality of life, and safety were also administered. The primary outcome was a validated subjective assessment for FoG (FOG-Q). Atomoxetine was well tolerated, however, no significant change was observed in the primary outcome. The gait analysis protocol correlated well with clinical scales, but not with subjective assessments. DBS patients were more likely to increase gait velocity (p = 0.033), and improved in other clinical assessments. Conclusions Objective gait analysis protocols assessing gait while dual tasking are feasible and useful for this patient population, and may be superior correlates of FoG severity than subjective measures. These findings can inform future trials in this population.